Evolution of the major alcohol companies key global policy vehicle through the prism of tax records 2011-19 - Matthew Lesch; Jim McCambridge (BMC, 2023)
Abstract Background Important insights have been generated into the nature of the activities of the International Center for Alcohol Policies (ICAP). Its successor, the International Alliance for Responsible Drinking (IARD) is less well understood. This study aims to rectify evidence limitations on the political activities of the alcohol industry at the global level. Methods Internal Revenue Service filings were examined for ICAP and IARD each year between 2011 and 2019. Data were triangulated with other sources to establish what could be gleaned on the internal workings of these organisations. Results The stated purposes of ICAP and IARD are near identical. The main declared activities were similar for both organisations and comprised public affairs/policy, corporate social responsibility, science/research and communications. Both organisations work extensively with external actors and it has become possible more recently to identify the main contractors supplying services to IARD. Discussion This study sheds light on the political activities of the alcohol industry at the global level. It suggests that the evolution of ICAP into IARD has not been accompanied by shifts in the organisation and activities of the collaborative efforts of the major alcohol companies. Conclusion Alcohol and global health research and policy agendas should give careful attention to the sophisticated nature of industry political activities.